Treatment of Community-Acquired Pneumonia: Are All Countries Treating Children in the Same Way? A Literature Review - Daniele Donà; Dora Luise; Liviana Da Dalt; Carlo Giaquinto (International Journal of Pediatrics)
Background. Pneumonia represents an important threat to children’s health in both developed and developing countries. In the last 10 years, many national and international guidelines on the treatment of pediatric CAP have been published, in order to optimize the prescription of antibiotics and limit their cost and side effects. However, the practical implementation of these guidelines is still limited. Main Text. We analyzed the current recommendations for the therapy of pediatric community-acquired pneumonia (CAP) that all converge on the identification of aminopenicillins and beta-lactams as the optimal treatment for CAP. We also conducted a review of the current literature on antibiotic regimens used for pediatric CAP to identify the current state of guidelines implementation in different settings. We selected 37 studies published from 2010 to 2016, including both retrospective and prospective studies, mainly cross-sectional and hospital based. The results show a global heterogeneity in the antibiotics prescription for pediatric CAP, with application of guidelines varying from 0% to more than 91% and with important differences even within the same country. Conclusions. Our review has demonstrated that the implementation of the guidelines is still limited but also that achieving the optimal prescription is possible and can be done in both developed and developing countries.